(untitled) (Third Sector Social Economic Review, 2024)
The Fourth Industrial Revolution, Industry 4.0, is characterized by various technological components such as big data, autonomous robots, cloud computing, and the Internet of Things (IoT). The integration of these Industry 4.0 components in production has brought about several advantages and disadvantages in terms of the global economy and competitiveness. Industry 4.0 has led to changes in factors that affect competitiveness, including institutions, financial systems, infrastructure, innovation capabilities, health, education, and macroeconomic variables. In the constantly evolving global economy, significant changes are observed in competition factors and in the creation of competitive quality and advantages. This research was planned with the hypothesis that the level of firms’ adaptation to these changes would impact their market and innovation performance. The study aimed to examine the relationships between Industry 4.0 applications, competitive strategies, market performance, and innovation performance through the lens of foreign trade firms. The research utilized quantitative methods, with a sample of 402 officials from foreign trade companies operating in Turkey in 2023, selected through a convenience sampling method. The study was designed as a relational survey model. Data were collected using a questionnaire that included a firm and participant information form, a competitive strategies scale, an Industry 4.0 applications scale, an innovation performance scale, and a market performance scale. The collected data were analyzed using SPSS 22.0 and AMOS 22 software. The relationships between variables were examined through correlation analysis and structural equation modeling. The findings revealed that, in foreign trade companies, most Industry 4.0 applications—except for big data, cyber-physical systems, IoT, cloud computing, and 3D printing—are only partially implemented. Furthermore, these companies lack awareness of robotic applications and augmented reality. It was concluded that foreign trade firms utilize all three competitive strategies at a high level, perceive their market performance as slightly improved, and rate their innovation performance as high. Industry 4.0 practices were found to have a partial effect on competitive strategies, market performance, and innovation performance. However, competitive strategies were determined to have significant effects on both market performance and innovation performance.